Acute mesenteric ischemia with tuberculous mesenteric lymphadenitis in a young female - Shreshtha, Suruchi; Sekhose, Ashu K.; S., Sujitha (International Surgery Journal, 2017)
We present the case of an 18 year old female with tuberculous mesenteric lymphadenopathy who came to hospital with peritonitis and acute mesenteric ischemia. An emergency exploratory laparotomy with resection of gangrenous small bowel and right colon with end-to-end anastomosis was performed. Subsequent evaluation for etiology of bowel gangrene was essentially normal. By exclusion, the most likely cause of acute mesenteric ischemia in this patient was of unknown etiology which is indeed rare. However, tuberculosis as a cause of mesenteric vasculitis and bowel gangrene needs to be explored.